Delta medicine : natural therapies for the five functions of cellular health - Rougier, Yann. (Rochester, Vt. : Healing Arts Press, 2012)
"A simple five-part program to awaken your self-healing potential at the cellular level gives your body the support it needs to control and reverse chronic and degenerative diseases such as cancer or multiple sclerosis. Provides anti-stress and anti-fatigue breathing practices, color-coded food guides, detoxification plans for specific organs, relaxation techniques, and creative psychological exercises to remove any blocks to your will to heal. Explains how these methods are completely compatible and safe to use with modern medical therapies, such as chemotherapy and radiation. Developed by French doctor Yann Rougier to reinforce health at the cellular level, where disease first manifests, Delta Medicine provides a simple, step-by-step method to awaken your self-healing potential and give your body the support it needs to control and reverse chronic and degenerative diseases such as cancer or multiple sclerosis. The Delta Medicine program addresses the five basic functions of a cell--breathing, nutrition, elimination of wastes, communication with other cells, and the creation and expression of emotions--with five corresponding practical tools: anti-stress and anti-fatigue breathing practices, color-coded food guides to develop the "reflexes" of healthy nutrition, targeted detoxification plans for specific organs, easy relaxation techniques to make peace with your illness and find calm during medical treatments, and creative psychological exercises to remove the unconscious blockages that often imprison your will to heal. An effective and perfectly safe complement to standard medical treatments, including chemotherapy and radiation, Delta Medicine's gentle transformations offer a way to actively participate in your own healing"--
""A simple five-part program to awaken your self-healing potential at the cellular level"--Provided by publisher"--
Includes bibliographical references (p. 230-239) and index.
Keywords: Cancer -- Alternative treatment; Cancer -- Diet therapy; Detoxification (Health); Cancer -- Psychosomatic aspects; HEALTH & FITNESS / Diseases / Cancer; HEALTH & FITNESS / Diseases / General; HEALTH & FITNESS / Holism